Predictors of asylum seekers' health care utilization in the early phase of resettlement - Kindermann, David; Zeyher, Valentina; Nagy, Ede; Friederich, Hans-Christoph; Bozorgmehr, Kayvan; Nikendei, Christoph (Frontiers in psychiatry, 2020)
Background: Asylum seekers display high prevalence rates of posttraumatic stress disorder, depression, anxiety, and panic disorder due to pre-, peri-, and post-migration stressors. In contrast to the high mental health burden, health care utilization among asylum seekers in the early phase of resettlement is low. However, the early stages after migration are a particularly vulnerable phase in which psychosocial support measures are needed to prevent mental disorders from becoming chronic. - Objective: To identify predictors of asylum seekers' health care utilization in the early stages of resettlement. - Methods: Using hierarchical logistic regression analysis, the variance explanation of the (1) general utilization of health care services as well as the individual utilization of (2) outpatient psychiatrists, (3) counselling centers, and (4) general practitioners was analyzed in n = 65 asylum seekers. A structured interview on health care utilization took place between three to five months after assessment of possible predictors. We defined the following three groups of predictors a) the sociodemographic variables gender, age, number of children, religion, language proficiency, b) the psychological variables sense of coherence and emotion regulation as well as c) the asylum seekers' psychiatric diagnoses. - Results: Individual sociodemographic factors, such as gender, age, and number of children as well as the emotion regulation strategy of expressive suppression and sense of coherence were shown to be predictive for the utilization of health care services among asylum seekers. - Conclusions: Low-threshold, culture-sensitive treatment offers for asylum seekers should be established in the early phase after migration. General practitioners should be a central hub for further referrals to disorder-specific treatments.
Gesehen am 04.08.2020